Bisphenol S induces obesogenic effects through deregulating lipid metabolism in zebrafish (Danio rerio) larvae. (May 2018) - Wang, Weiwei; Zhang, Xiaona; Wang, Zihao; Qin, Jingyu; Wang, Wei; Tian, Hua; Ru, Shaoguo
Abstract: It has been suggested that dramatic increase in obesity may be caused by growing exposure to environmental chemicals. In vitro data has suggested bisphenol S (BPS), a compound widely used in polycarbonate plastic production, can induce lipid accumulation in preadipocytes. However, the mechanisms responsible for BPS-induced obesity in vivo remain unclear. In this study, we used translucent zebrafish ( Danio rerio ) larvae as a model to investigate the effect of environmentally relevant BPS exposure (1, 10, and 100 μg/L from 2 h to 15 d post fertilization) on lipid accumulation, triacylglycerol (TAG) and lipoproteins content, and mRNA expression of genes involved in the regulation of lipid synthesis, transport, degradation, and storage. We also analyzed activities of two enzymes critical to TAG metabolism: lipoprotein lipase and diglyceride acyltransferase. Overfed, obese larvae were used as positive control. The results indicated that BPS-treated and overfed larvae had much higher TAG levels and visceral fat accumulation compared with control. BPS exhibited obesogenic effects by interfering with lipid metabolism as evidenced by (a) upregulation of the mRNA expression of fasn, acc1, and a gpat4 genes encoding enzymes involved in the de novo synthesis of TAG in the liver, (b) downregulation of apolipoprotein expression, which should reduce TAG transport from the liver, and (c) increase in rxrα expression, which should promote visceral fat accumulation. Our study is the first to demonstrate that the obesogenic effects of BPS in zebrafish are related to the disruption of TAG metabolism. Highlights: BPS increases visceral fat deposition and TAG levels in zebrafish larvae. BPS promotes transcription of genes involved in TAG synthesis. BPS deregulates transcription of genes involved in TAG transport. BPS-induced and diet-induced obesogenic effects are caused by distinct mechanisms.